The symphony orchestra in the Philippines: a cultural outline (1896-1986) - Martinez, Edna Marcil Morato
This paper is a study on the culture of the Philippine sy1nphony orchestra as it developed in Manila between 1896-1986, focusing on selected orchestral organizations from the post WWll and later periods. Interest of the study cover questions such as - how do these groups serve in the greater society? Have these organizations developed practices and relationships from the membership that are unique in their social setting? Why are individuals attracted to become part of these organizations? Why do groups continue to invest in these musical organizations in spite of difficulties in maintaining such organizations?